Valence band anticrossing model for GaSb1−xBix and GaP1−xBix using k.p method. (December 2015) - Samajdar, D.P.; Das, T.D.; Dhar, S.
Abstract: The reduction in band gap as well as the increase in spin–orbit splitting energy in GaSb1− x Bi x and GaP1−x Bix are explained by the Valence Band Anticrossing (VBAC) model. This restructuring of the valence band is due to the interaction of the Bi related impurity levels with the extended states of the valence band of the host semiconductor. The band gap reduction in GaSb1− x Bi x and GaP1− x Bi x calculated using VBAC model are respectively 40.2 meV and 206 meV/at% Bi. A comparison of the theoretical and experimentally obtained values of band gap in GaSbBi shows good agreement. Valence band structure for GaPBi is obtained by the extrapolation of the parameters used for modeling of the GaSbBi system. The upward movement of the spin–orbit split-off E+ energy level in GaSbBi by 19.2 meV/at% Bi is also responsible for the suppression of Auger recombination processes making it a potential candidate for near and mid-infrared optoelectronic applications.